User behavior based call admission control for traffic steering in Wi-Fi/cellular networks - Lim, Yun Yi; Mohd Shariff, Azizul Rahman; Mohd Zaini, Khuzairi (Universiti Utara Malaysia Press, 2015)
The expanded growth in smartphones and applications, hence data traffic resulted in cellular networks being conspicuously overwhelmed with demand for resources. Service providers constantly looking for suitable technologies and mechanisms to reduce the network congestion by offloading the data traffic, where Wi-Fi is an excellent option. In the traffic steering process, network selection is the most vital process, as it affects the user’s network experience. This paper focuses on enhancing the procedure of Call Admission Control (CAC). Two key functions were introduced into the call admission procedure, namely Channel Reserve Engine (CRE) and Traffic Steering Policy (TSP). Based on the simulation results, it is found the proposed CAC reduces the call blocking probability as compared with conventional CAC. Thus, it is suitable to be implemented in WLAN/Cellular integration.